Multifunctional Electronic Media-Traditional Media. - Hischier, Roland (The International Journal of Life Cycle Assessment)
Aim and Background. Electronic media are spreading rapidly and some of the services they offer are similar to traditional media. Frequently, credit is given to electronic media for causing less environmental impact, however, looking at it more closely, little is known about the comparability of the environmental impact of both kinds of media. Main reasons for this lack of knowledge are difficulties in defining an adequate functional unit for a comparison of usually multifunctional media, as well as problems in gathering large amounts of inventory data for complex electronic goods. Objective. Here an LCA case study was conducted for reading or watching the daily news in an online and a printed newspaper as well as on TV. Aim of this study was to find an adequate functional unit as well as to quantify the environmental impact of each of the media, including recommendations for the reduction of their impact. In order to account for the multifunctionality of the investigated media as well as for ISO 14040ff. guidelines for the definition of the functional unit, several functional units were chosen. The selected functional units cover a spectrum of close functional equivalence to an altogether different approach in comparing entire activities. Results. Compared on the basis of an average news item, the internet newspaper causes far more environmental impact than ting of a newspaper. Major contributions to the high environmental impact of the internet newspaper are the manufacturing of the computer as well as operation of the necessary infrastructure for running the internet, in particular operation of the telephone network. Comparing media on the basis of consuming the daily news as a whole leads to less environmental impact for both of the electronic media in relation to a printed newspaper, even if shared amongst several readers. The comparative environmental advantage of the electronic media depends on a set of conditions : 1. No online information is printed. 2. Internet surfing is directed towards specific goals and therefore limited in time. 3. Power consumption is based to a large extent on renewable energy sources. This still holds true for the underlying national electricity mix of Switzerland with a high share of hydropower. A comparison of the average per capita time of watching TV with surfing in the internet and average paper consumption of free and bought print products also shows that most of the environmental impact results from print products. Interpretation. Summarising the previously shown results, different perspectives on media and, with it, different functional units lead-not surprisingly- to different results. Relations between the environmental impact of the three media change between approaches. A final conclusion on a qualitative level is drawn. The first functional unit stands for close functional equivalence, however, it does not resemble options of the consumer in real life. The cuttings of a newspaper cannot be bought as such and the consumer is normally not interested in a single news item. The second functional unit is more of a representation of real life choices and is a typical example of a consumer's choice that frequently has to decide between options which are not exactly functionally equivalent. Finally, the last approach, based on entire activities, supports the result of the previous approach. Perspective. The case study has shown that a comparison of multifunctional products or services excludes relevant environmental aspects, if functional equivalence is chosen as the unique reference unit. Thus, it is recommended to apply several approaches in order to do justice to the multifunctionality of the investigated products or services. ISO/TR 14049, with its concept of user acceptance, offers such a possibility to compare products or services which are still considered equivalent by the user.